2021
DOI: 10.1503/jpn.190139
|View full text |Cite
|
Sign up to set email alerts
|

The role of anthranilic acid in the increase of depressive symptoms and major depressive disorder during treatment for hepatitis C with pegylated interferon-α2a and oral ribavirin

Abstract: Background: Tryptophan metabolism via the kynurenine pathway is considered the link between the immune and endocrine systems. Dysregulation of serotonergic transmission can stem from the direct influence of interferon-α on the activity of serotonergic receptors 5-HT 1A and 5-HT 2A , and from its indirect effect on tryptophan metabolism. Induction of the kynurenine pathway increases the concentration of neurotoxic kynurenine metabolites, and the activity of kynurenine derivatives is linked to the onset of depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Authors found that elevation of plasma AA (but not other studied Kyn derivatives) was the best negative prognostic marker for unfavorable course of disease (e.g., transfer to ICU, mechanical ventilation, death) in COVID-19 patients. The discovery of elevated AA plasma levels in prospective study of COVID-19 patients [19] is in line with finding of elevated plasma AA levels in prospective study of hepatitis C patients treated with interferon-alpha [21]. Notably, IFNG activates kynase, the enzyme that catalyzes AA formation from Kyn [22].…”
Section: Sars-cov-2 Infection and Down-stream Kynurenine Metabolismsupporting
confidence: 66%
See 1 more Smart Citation
“…Authors found that elevation of plasma AA (but not other studied Kyn derivatives) was the best negative prognostic marker for unfavorable course of disease (e.g., transfer to ICU, mechanical ventilation, death) in COVID-19 patients. The discovery of elevated AA plasma levels in prospective study of COVID-19 patients [19] is in line with finding of elevated plasma AA levels in prospective study of hepatitis C patients treated with interferon-alpha [21]. Notably, IFNG activates kynase, the enzyme that catalyzes AA formation from Kyn [22].…”
Section: Sars-cov-2 Infection and Down-stream Kynurenine Metabolismsupporting
confidence: 66%
“…The recent prospective study found elevation of plasma AA as predictor of increased risk of major depressive disorder in interferontreated hepatitis C virus patients [21]. AA plasma levels were associated with severity of depression symptoms in female patients with no clinical and biochemical signs of inflammation [41].…”
Section: Psychiatric Conditions Associated With Trp -Kyn Pathway Dysregulations In Interferon-treated Patientsmentioning
confidence: 99%
“…This finding may suggest that AntA level could mirror the depression severity and should be investigated in a larger population. Increased AntA levels have been reported in different mental disorders such schizophrenia ( 83 ) and MDD ( 55 ) as well as metabolic disorders including chronic hepatitis C, rheumatoid arthritis and osteoarthritis ( 84 ) and type 1 diabetes ( 85 , 86 ). A clinical study reported that blood serum level of AntA may predict the onset and progression of clinical depression ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an increase in AntA concentration was associated with decreased levels of anti-inflammatory factors in high risk MDD subjects. Pawolwski et al ( 86 ) provided first direct evidence of a role for anthranilic acid in the pathogenesis of inflammation-induced MDD ( 86 ). Generally, downstream metabolites of the kynurenine pathway and availability of tryptophan play critical role for the functioning of efferent nerve system and CNS and thus in the gut-brain communication.…”
Section: Discussionmentioning
confidence: 99%
“…26 The TDO enzyme is under the influence of 4 regulatory mechanisms in the liver: hormonal (glucocorticoids, glucagon, and estrogens); stabilization by tryptophan against degradation; inhibition by intermediate products of tryptophan metabolism; and activation by haem. 27 The first catabolite in tryptophan metabolism governed by the IDO1/2 and TDO enzymes is kynurenine (KYN), which further yields kynurenic acid (KYNA) 28 (via kynurenine aminotransferases [KATs]), anthranilic acid (via kynureninase [KYNU]) 29 or 3-hydroxykynurenine (3-HK) via kynurenine 3-monooxygenase (KMO). 30 In the next stage of Trp metabolism, both anthranilic acid (through non-specific hydroxylation) and 3-HK (via KYNU) serve as sources for the production of 3-hydroxyanthranilic acid (3HAA).…”
Section: Tryptophan Metabolism and The Kynurenine Pathwaymentioning
confidence: 99%